2022
DOI: 10.4049/jimmunol.2100969
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Quiescence and Longevity of IgG Memory B Cells by Mitochondrial Autophagy

Abstract: The development of long-lived immune memory cells against pathogens is critical for the success of vaccines to establish protection against future infections. However, the mechanisms governing the long-term survival of immune memory cells remain to be elucidated. In this article, we show that the maintenance mitochondrial homeostasis by autophagy is critical for restricting metabolic functions to protect IgG memory B cell survival. Knockout of mitochondrial autophagy genes, Nix and Bnip3, leads to mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…B220 + CD3 -CD27 + memory B cells were also assessed in our study. These antigenspecific memory cells were first described over 20 years ago and are responsible for quick response upon antigen restimulation by switching to a B220 low phenotype [74,75]. This may indicate that EXP-2.3 was sensitized to OVA during the CD, which has been observed in previous studies in our group [32] and also in the literature [76,77].…”
Section: Discussionsupporting
confidence: 79%
“…B220 + CD3 -CD27 + memory B cells were also assessed in our study. These antigenspecific memory cells were first described over 20 years ago and are responsible for quick response upon antigen restimulation by switching to a B220 low phenotype [74,75]. This may indicate that EXP-2.3 was sensitized to OVA during the CD, which has been observed in previous studies in our group [32] and also in the literature [76,77].…”
Section: Discussionsupporting
confidence: 79%
“…Mice lacking mitochondrial autophagy genes accumulate mitochondria and experience oxidative phosphorylation and fatty acid synthesis, leading to the loss of B memory cells. 188 Similarly, autophagy facilitates the differentiation of monocytes to macrophages stimulated by colony-stimulating factor 1 (CSF1) and CSF2. Mechanically, CSF1 promotes autophagy by increasing the expression and phosphorylation of ULK1.…”
Section: Autophagy Synergizes Antitumor Immune Responsementioning
confidence: 99%
“…In this study, we find that patients with PD display lower levels of memory CD8 + T cells in the circulation and fail to generate similar levels of spike protein–specific memory CD8 + T cells upon SARS-CoV-2 vaccination. A recent study reported that genetic ablation of BNIP3 and NIX can lead to decline of memory B cell populations in mice via undefined mechanisms, suggesting that mitophagy also plays a critical role in maintaining memory B cells ( 58 ). Therefore, we speculate that patients with PD might also display reduced memory B cell responses.…”
Section: Discussionmentioning
confidence: 99%